Truncated Variants of Gaussia Luciferase with Tyrosine Linker for Site-Specific Bioconjugate Applications - Hunt, Eric A. (Sci Rep, 2016)
Gaussia luciferase (Gluc)—with its many favorable traits such as small size, bright emission, and exceptional stability—has become a prominent reporter protein for a wide range of bioluminescence-based detection applications. The ten internal cysteine residues crucial to functional structure formation, however, make expression of high quantities of soluble protein in bacterial systems difficult. In addition to this challenge, the current lack of structural data further complicates the use of Gluc for in vitro applications, such as biosensors, or cellular delivery, both of which rely heavily on robust and reproducible bioconjugation techniques. While Gluc is already appreciably small for a luciferase, a reduction in size that still retains significant bioluminescent activity, in conjunction with a more reproducible bioorthogonal method of chemical modification and facile expression in bacteria, would be very beneficial in biosensor design and cellular transport studies. We have developed truncated variants of Gluc, which maintain attractive bioluminescent features, and have characterized their spectral and kinetic properties. These variants were purified in high quantities from a bacterial system. Additionally, a C-terminal linker has been incorporated into these variants that can be used for reliable, specific modification through tyrosine-based bioconjugation techniques, which leave the sensitive network of cysteine residues undisturbed.